A botanical drug composed of three herbal materials attenuates the sensorimotor gating deficit and cognitive impairment induced by MK‐801 in mice. (12th November 2019) - Koo, Bokyung; Bae, Ho Jung; Goo, Nayeon; Kim, Jaehoon; Kim, Jihyun; Cai, Mudan; Jung, In Ho; Cho, Kyungnam; Jung, Seo Yun; Chang, Suk Woo; Jang, Dae Sik; Ryu, Jong Hoon
Abstract: Objectives: A botanical drug derived from the ethanolic extract composed of Clematis chinensis Osbeck (Ranunculaceae), Trichosanthes kirilowii Maximowicz (Cucurbitaceae) and Prunella vulgaris Linné (Lamiaceae) has been used to ameliorate rheumatoid arthritis as an ethical drug in Korea. In our study, we investigated the effect of this herbal complex extract (HCE) on schizophrenia‐like behaviours induced by MK‐801. Methods: HCE (30, 100 or 300 mg/kg, p.o) was orally administered to male ICR mice to a schizophrenia‐like animal model induced by MK‐801. We conducted an acoustic startle response task, an open‐field task, a novel object recognition task and a social novelty preference task. Key findings: We found that a single administration of HCE (100 or 300 mg/kg) ameliorated MK‐801‐induced abnormal behaviours including sensorimotor gating deficits and social or object recognition memory deficits. In addition, MK‐801‐induced increases in phosphorylated Akt and GSK‐3β expression levels in the prefrontal cortex were reversed by HCE (30, 100 or 300 mg/kg). Conclusions: These results imply that HCE ameliorates MK‐801‐induced dysfunctions in prepulse inhibition, social interactions and cognitive function, partly by regulating the Akt and GSK‐3β signalling pathways.